Sadgati - Ray, Satyajit; Roy, Soumendu; Puri, Om; Patil, Smita; Agashe, Mohan
Untouchable shoemender Dukhi comes to the Brahmin's and asks him to arrange his daughter's engagement. The Brahmin belongs to a higher caste. He wants Dukhi to work for him (and for free) before agreeing ... A plea against the indian system of castes. [www.imbd.de]